INTEGRATION OF SPORTS AND TOURISM IN STRENGTHENING YOUTH HEALTH - Aslanova Maloxat Akramovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the role of integrating sports and tourism in strengthening the physical and mental health of young people. The study highlights how combined sports and tourism activities promote physical fitness, psychological wellbeing, and social engagement among youth. The article also discusses effective approaches for implementing integrated programs that encourage active lifestyles and support sustainable youth health development.